Influences of eye gaze cues on memory and its mechanisms: The function and evolution of social attention - Yin, Xiyang (Frontiers in Psychology, 2022)
During evolution, humans have formed a priority perceptual preference for others’ gazes. The gaze direction of others is called the gaze cue, conveying environmental information, a critical non-verbal communication in early humans. Recently, empirical evidence has indicated that gaze cues can affect high-level cognitive processes, such as memory. Unlike non-social cues (e.g., arrows), gaze cues elicit special social attention. Research determining the underlying mechanisms suggests that social intention influences observers’ visual attention and influences their memory. This article provides a brief review of the current state of research on the relationship between gaze cues and memory. Future studies should focus on multiple gaze cues, the social nature of gaze cues, and clinical research.